The Mediatization of the O.J. Simpson Case From Reality Television to Filmic Adaptation - Neubauer, Tatjana (Edition Medienwissenschaft, 2023)
F. Scott Fitzgerald once said: »Show me a hero, and I'll write you a tragedy.« In the 1990s, nobody fell deeper than O.J. Simpson. Once considered a national treasure, the athlete was accused of brutally slaying his ex-wife Nicole Brown and her friend Ronald Goldman on June 12, 1994. Within days, the media and public developed an unprecedented obsession with the story, turning a murder investigation and trial into a sensationalized reality show. Tatjana Neubauer examines the mediatization, deliberate manipulation, and the simplification of popular criminal trials for profit on television. She demonstrates that TV conflated legal proceedings into entertainment programming by commodifying events, people, and places.